The Semantic Web: ESWC 2011 Workshops Workshops at the 8th Extended Semantic Web Conference, ESWC 2011, Heraklion, Greece, May 29-30, 2011, Revised Selected Papers - Garcia-Castro, Raul; Fensel, Dieter; Antoniou, Grigoris (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This volume constitutes the thoroughly refereed proceedings of 11 international workshops held as part of the 8th Extended Semantic Web Conference, ESWC 2011, in Heraklion, Crete, Greece, in May 2010. The 22 revised full papers presented were carefully reviewed and selected from a total of 75 submissions to the workshops during two rounds of reviewing and improvement. The papers are organized in topical sections on the following workshops: 1st International Workshop on eLearning Approaches for the Linked Data Age, 1st Workshop on High-Performance Computing for the Semantic Web, 3rd International Workshop on Inductive Reasoning and Machine Learning for the Semantic Web, 1st Workshop on Making Sense of Microposts, 1st Workshop on Ontology and Semantic Web for Manufacturing, 1st Workshop on Question Answering over Linked Data, 4th International Workshop on REsource Discovery, 6th International Workshop on Semantic Business Process Management, 1st Workshop on Semantic Publication, 1st Workshop on Semantics in Governance and Policy Modelling, and 1st International Workshop on User Profile Data on the Social Semantic Web.